Evaluation of factors associated with sexual dysfunction in psoriasis in a cohort of 1409 patients. (2nd February 2022) - Salle, Romain; Taïeb, Charles; Aubert, Roberte; Heller, Ugo; Halioua, Bruno; Shourick, Jason
Abstract : We report on the sexual disorders common in patients with psoriasis, and examine the underlying reasons, including the use of psoriasis treatments that can result in sexual difficulties.